Impact of Gemcitabine Chemotherapy and 3-Dimensional Conformal Radiation Therapy/5-Fluorouracil on Quality of life of patients Managed for Pancreatic Cancer - Short, Michelle; Goldstein, D.; Halkett, Georgia; Reece, W.; Borg, M.; Zissiadis, Y.; Kneebone, A.; Spry, Nigel (Elsevier Inc., 2013)
Purpose: To report quality of life (QOL) results for patients receiving chemoradiation therapyfor pancreatic cancer.Methods and Materials: Eligible patients (nZ41 locally advanced, nZ22 postsurgery) enteredthe B9E-AY-S168 study and received 1 cycle of induction gemcitabine (1000 mg/m2 weekly 3with 1-week break) followed by 3-dimensional conformal radiation therapy (RT) (54 Gy locallyadvanced and 45 Gy postsurgery) and concomitant continuous-infusion 5-fluorouracil (5FU)(200 mg/m2/d throughout RT). After 4 weeks, patients received an additional 3 cycles of consolidationgemcitabine chemotherapy. Patients completed the European Organization for Researchand Treatment of Cancer QLQ-C30 and QLQ-PAN26 questionnaires at baseline, beforeRT/5FU, at end of RT/5FU, before consolidation gemcitabine, and at treatment completion.Results: The patterns of change in global QOL scores differed between groups. In the locallyadvanced group global QOL scores were þ13, þ8, þ3, and þ1 compared with baseline beforeRT/5FU (PZ.008), at end of RT/5FU, before consolidation gemcitabine, and at treatmentcompletion, respectively. In the postsurgery group, global QOL scores were 3, þ4, þ15,and þ17 compared with baseline at the same time points, with a significant improvement inglobal QOL before consolidation gemcitabine (PZ.03). No significant declines in globalQOL were reported by either cohort.